Sustainable behavior: promotion of environmental awareness through gymkhana (Research, Society and Development, 2020)
This paper proposes the use of a gymkhana hunt as a way to implement an environmental and sustainable awareness in the school community of Estrela Dalva (MG). The article has a quantitative and qualitative approach that discusses the environmental education theme in the school space effectively, promoting interdisciplinarity. The gymkhana hunt demonstrated possibilities and the importance of recycling materials that were previously destined for garbage or wrong disposal, creating workshops that work (e.g turning cooking oil into soap, pet bottles into furniture and decorative paintings etc.) these skills. Exposing these activities as a science fair and then creating a march for sustainability were strategies adopted to bring knowledge of the five R's to the community, demonstrating that the school also has its social role.